Economic regions in Asia Pacific: An exercise in regional delimitation - Torsten Amelung (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
The export oriented economies in East and Southeast Asia have formed one of the most vibrant regions in the world. Due to their openness they have enjoyed increasing shares in world trade. Concomitant with their integration into the world market, the countries of the region have developed closer economic relations in terms of trade links and financial interdependence among each other. Especially, the governments of the ASEAN countries are pursuing a strategy of explicitly encouraging the exchange of goods and factors of production by extending regional trade preferences to each other as well as through other measures of industrial and financial cooperation (See Devan, 1987; Hiemenz, Naya, 1985; Amelung, 1989). For some ASEAN members, however, bilateral economic relations with non-member countries such as the USA, Japan, Taiwan, Hong Kong and South Korea have still remained more important than those within the ASEAN group.
Keywords: 330; Wirtschaftsraum; Clusteranalyse; Asiatisch-pazifischer Raum